Prognostic factors in pemphigus vulgaris and pemphigus foliaceus. (1st January 2014) - Saha, M.; Bhogal, B.; Black, M.M.; Cooper, D.; Vaughan, R.W.; Groves, R.W.
Summary: Background: Pemphigus typically has a chronic course, although there is great variability in disease duration (DD) and time taken to disease remission (DR) between individuals with the disease. The reasons for this are unclear. Objectives: To explore the prognostic influence of epidemiological, clinical, immunological and genetic factors on disease course and remission in pemphigus vulgaris (PV) and pemphigus foliaceus (PF). Methods: This was a retrospective study of patients with PV and PF, recruited from a single UK centre. Direct and indirect immunofluorescence and enzyme‐linked immunosorbent assay studies for antidesmoglein (Dsg) antibodies were used to assess immunological factors. Polymerase chain reaction with sequence specific primers (PCR‐SSP) was used to assess the Class II human leukocyte antigen status of patients. Prognostic endpoints investigated were time to initial first DR and total DD. Results: Ninety‐five patients were recruited (79 PV and 16 PF). Patients of Indo‐Asian origin were significantly associated with longer DD than White‐British patients ( P = 0·029). In addition, younger age at onset was associated with a worse prognosis in terms of DD: the mean age at presentation of patients with DD of < 5 years was 49 years (SEM = 3·4) compared with 40 years (SEM = 1·9) in those with DD > 5 years ( P = 0·039). A higher initial intercellular antibody titre on normal human skin substrate was associated with a greater time to initial DR ( P = 0·007) and high anti‐Dsg 3 levels at baseline were associated with a longer total DD ( P = 0·03). Conclusions: Ethnic group, age at presentation, initial intercellular antibody titre and initial Dsg 3 antibody levels all had a significant impact on prognosis of pemphigus.